2013
DOI: 10.1002/jnr.23183
|View full text |Cite
|
Sign up to set email alerts
|

γ‐Aminobutyric acid‐ρ expression in ependymal glial cells of the mouse cerebellum

Abstract: The ependymal glial cells (EGCs) from the periventricular zone of the cerebellum were studied to determine their distribution and the functional properties of their γ-aminobutyric acid type A (GABA(A) ) receptors. EGCs were identified by the presence of ciliated structures on their ventricular surface and their expression of glial fibrillary acidic protein (GFAP). Interestingly, diverse cell types, including neurons, astrocytes, and other types of glia, were identified in the subventricular zone by their curre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
27
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 25 publications
2
27
0
1
Order By: Relevance
“…It has been shown previously that the subventricular zone of the cerebellum exhibits a diversity of cells that display different electrophysiological characteristics1. Whole-cell patch-clamp revealed that electric responses obtained from the subventricular zone of the cerebellum, which corresponds to lobes I and X, include neurons, astrocytes, oligodendrocytes and stem-cell like cells1.…”
mentioning
confidence: 99%
“…It has been shown previously that the subventricular zone of the cerebellum exhibits a diversity of cells that display different electrophysiological characteristics1. Whole-cell patch-clamp revealed that electric responses obtained from the subventricular zone of the cerebellum, which corresponds to lobes I and X, include neurons, astrocytes, oligodendrocytes and stem-cell like cells1.…”
mentioning
confidence: 99%
“…These cells generate GABA currents on exogenous administration of GABA owing to the presence of an array of GABA-A subunits that include GABAρ. GABA responses are partially blocked by TPMPA or bicuculline and totally abolished by a combination of the two compounds (10). Here we present evidence that during postnatal development of the cerebellum, GABAρ subunits are widely expressed in EGCs and even in GFAP + cells of the GL and subventricular zone.…”
Section: Discussionmentioning
confidence: 53%
“…Expression of GABAα1 is crucial for proper GABAergic neurotransmission in the cerebellum (24), and this subunit is known to be present mainly in the adult neurons with scattered expression in GFAP + cells (10). At P5 and P10, immunolabeling for GABAα1 was present mainly in non-GFAP + cells, although Bergmann glial processes in the close vicinity of Purkinje cells exhibited limited immunolabeling at P5 (Fig.…”
Section: Gaba-a Receptors In Cerebellar Gfapmentioning
confidence: 99%
See 2 more Smart Citations